Islamic Right for Women to Claim their Husband’s EPF Contribution according to Maqasid Sharia - Md Yazid Ahmad; Muhammad Adilah Supardan; Nurul Ilyana Muhd Adnan; Nor Adila Mohd Noor; Adibah Sulaiman (Human Resource Management Academic Research Society, 2024)
Indexed by ERA